PENINGKATAN KEMAMPUAN TAKTIL ANAK AUTIS MELALUI TERAPI SENSORI INTEGRASI - Nur Hafidzah Tanawali; Haerani Nur; Kurniati Zainuddin (Jurnal Psikologi TALENTA, 2018)
Tactile dis ability was one of the sensory problems experienced by children with special needs. Sensory integration therapy was used as a therapy for children with sensory processing problems. The aims of this study were to screen the effectiveness of sensory integration therapy to improve tactile abilities of autistic examine children. A repeated treatment experimental research design was used in this study. The subjects of this study consisted of 6 children with tactile sensory impairment. The measurement of sensory integration therapy was done by direct observation that when the children were given toys and learning tools. Results thus far indicate there is a difference in tactile ability before and after the therapy. Autistic children who have attended therapy have an increased ability of tactile. This research have implications for the therapy and parents to provide sensory integration therapy for children with low tactile ability.